Fecal Colonization With Multidrug-Resistant E. coli Among Healthy Infants in Rural Bangladesh - Islam, Mohammad Aminul; Amin, Mohammed Badrul; Roy, Subarna; Asaduzzaman, Muhammad; Islam, Md. Rayhanul; Navab-Daneshmand, Tala; Mattioli, Mia Catharine; Kile, Molly L.; Levy, Karen; Julian, Timothy R. (Frontiers in Microbiology, 2019)
Third generation cephalosporins (3GC) are one of the main choices for treatment of infections caused by multidrug-resistant Gram-negative bacteria. Due to their overuse, an increasing trend of resistance to 3GC has been observed in developing countries. Here, we describe fecal colonization of 3GC-resistant (3GCr) E. coli in healthy infants (1-12 months old) living in rural areas of Bangladesh. We found that stool samples of 82% of infants (n=100) were positive for 3GCr E. coli with a mean ± standard deviation of 6.21 ± 1.32 log10 CFU/g wet weight of stool. 3GCr E. coli encompasses an average one third (33%) of the total E. coli of stool. Almost 77% (n=63) of these 3GCr E. coli were multidrug-resistant (or resistant to ≥3 classes of antibiotics). Around 90% (n=74) of 3GCr E. coli were extended spectrum beta-lactamase (ESBL)-producing in which blaCTX-M-group-1 was the predominant (96%, n=71) ESBL-gene followed by blaTEM (41%, n=30) and blaOXA-1 (11%, n=8). A significant proportion (26.5%, n=22) of 3GCr E. coli was pathogenic, comprising two types, enteroaggregative (EAEC, n=19) and enteropathogenic (EPEC, n=3). Colonization of 3GCr E. coli in infant guts was not associated with demographic characteristics such as age, sex, mode of delivery, maternal and infant antibiotic use, disease morbidity, and feeding practices. The high rate of colonization of 3GCr E. coli in infants’ guts is a serious public health concern which needs immediate attention and warrants further studies to explore the cause.